Penerapan Intervensi Kombinasi Aromaterapi Lemon dan Guided Imagery dalam Asuhan Keperawatan pada Klien dengan Diagnosis Medis Post Operasi Open Reduction Internal Fixation Fraktur Ekstremitas Hari Ke-1 di Bangsal Bedah RSUD Sleman - Vernanda, Gilang Adi; Sari, Ike Wuri Winahyu; Pratiwi, Pratiwi (HEALTHY BEHAVIOR JOURNAL, 2024)
Background: Bone fracture is one of the most common injuries with a global prevalence in 2020 reaching 2.7% with 1.3 million fracture cases occurring annually in Indonesia. Postoperative pain is one of the impacts felt by patients. One pain management that can be done is non-pharmacological management by providing combination therapy between aromatherapy and guided imagery. However, this pain management needs to be studied further because differences in patient characteristics influence the response to each therapy given. Objective: To find out the application of combination therapy between aromatherapy and guided imagery in reducing pain levels. Case Report: This study is a case report with a 21-year-old male patient who came to the emergency department due to a traffic accident. The nursing diagnosis made in this patient was acute pain related to physical injury agents and the medical diagnosis was post-operative open reduction internal fixation (ORIF) cruris and right clavicle. The non-pharmacological management provided is in the form of aromatherapy using a diffuser containing 50 ml of water and 5 drops of lemon aroma essential oil, as well as guided imagery. Pain level evaluation was carried out before and after the intervention. Results: The application of lemon aromatherapy and guided imagery is effective in reducing post-operative pain, as evidenced by the pain scale being reduced from 8 to 3. Conclusion: The application of combination therapy between aromatherapy and guided imagery is effective in reducing pain levels in post-operative patients.